New material perspective for endocrown restorations: effects on mechanical performance and fracture behavior - José Augusto SEDREZ-PORTO; Eliseu Aldrighi MÜNCHOW; Lisia Lorea VALENTE; Maximiliano Sergio CENCI; Tatiana PEREIRA-CENCI (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract The aim of this study was to investigate the mechanical performance and the fracture behavior of endocrown restorations prepared using distinct restorative materials. A total of 42 sound molars with similar crown size and shape were cut at 2 mm above the cementoenamel junction and endodontically treated. They were categorized according to the restorative material used to fabricate endocrown restorations (n=7), namely, conventional composite (Filtek™ Z350 XT), bulk fill composite (Filtek™ Bulk Fill), conventional composite modeled using resin adhesives (SBMP: Scotchbond™ Multipurpose Adhesive; or SBU: Scotchbond™ Universal Adhesive), and IPS e.max lithium disilicate (Ivoclar Vivadent; positive control). Unprepared sound teeth were used as negative control. All endocrowns were bonded using a self-adhesive cement (Rely-X™ U200). The teeth were submitted to fatigue (Byocycle) and fracture (EMIC DL500) testing. Load-to-fracture (in N) and work-of-fracture (Wf, in J/m2) values were analyzed by ANOVA (p < 0.05). The endocrowns did not fracture or de-bond upon fatigue, showing similar load-to-fracture and work-of-fracture values, regardless of the restorative material (p > 0.05). The endocrowns fabricated by combining Z350 and SBMP had the least harsh fractures, in contrast to endocrowns prepared using Z350 only, which exhibited an equilibrium between repairable and irrepairable fractures. The e.max endocrowns exhibited more aggressive failures (root fracture) than other groups, resulting in higher rates of irrepairable fractures. In conclusion, dental practitioners may satisfactorily restore severely damaged nonvital teeth using the endocrown technique. Composite endocrowns prepared using resin adhesive as modeler liquid or using bulk fill material may result in less aggressive failures, thus providing a new material perspective for endocrown restorations.